1978
DOI: 10.1128/aem.35.1.124-128.1978
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transformations of styrene and [14C] styrene in soil and enrichment cultures

Abstract: Two different mechanisms were responsible for the disappearance of styrene in enrichment cultures: (i) a mixed population of microorganisms, capable of utilizing styrene as a sole carbon source, oxidized this substrate to phenylethanol and phenylacetic acid; (ii) the culture also mediated polymerization of the monomer to low-molecular-weight styrene oligomers. This chemical reaction probably occurred as the result of microbial degradation of butylcatechol, an antioxidant polymerization inhibitor present in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…These compounds have both been proposed as initial transformation products in the aerobic degradation of styrene (Fig. 2) (11,13). Although both styrene oxide and 2-phenylethanol were oxidized by styrenegrown cells (Table 1) Reactions: 1, oxidation of styrene to styrene oxide by a Pseudomonas sp.…”
Section: Downloaded Frommentioning
confidence: 98%
“…These compounds have both been proposed as initial transformation products in the aerobic degradation of styrene (Fig. 2) (11,13). Although both styrene oxide and 2-phenylethanol were oxidized by styrenegrown cells (Table 1) Reactions: 1, oxidation of styrene to styrene oxide by a Pseudomonas sp.…”
Section: Downloaded Frommentioning
confidence: 98%
“…Alternative routes for aerobic microbial degradation of styrene have been described earlier. Degradation of styrene by enrichment cultures was shown to yield 2-phenylethanol and phenylacetate [1]. 2-Phenylethanol was produced from styrene by pure bacterial cultures as well [21.…”
Section: Introductionmentioning
confidence: 99%
“…Initial attempts to isolate organisms that could grow on styrene were unsuccessful, probably because the concentrations of styrene used for the isolation were too high, for example 0.1 mol styrene 1-' used by Sielicki et al (1978a).…”
Section: I C R O B I a L M E T A B O L I S M Of Styrenementioning
confidence: 99%
“…The majority of organisms investigated have been found to use a pathway which converts styrene to 2-phenylethanol or phenylacetic acid. Sielicki et al (1978a) isolated a mixed culture which could degrade styrene, and found that phenylacetic acid and 2-phenylethanol were present in the growth medium. Shirai and Hisatsuka (1979a) isolated…”
Section: Breakdown Via Phenylacetic Acidmentioning
confidence: 99%